Encapsulated Urea-Kaolinite Nanocomposite for Controlled Release Fertilizer Formulations - Siafu Ibahati Sempeho; Hee Taik Kim; Egid Mubofu; Alexander Pogrebnoi; Godlisten Shao; Askwar Hilonga (Journal of Chemistry)
Urea controlled release fertilizer (CRF) was prepared via kaolinite intercalation followed by gum arabic encapsulation in an attempt to reduce its severe losses associated with dissolution, hydrolysis, and diffusion. Following the beneficiation, the nonkaolinite fraction decreased from 39.58% to 0.36% whereas the kaolinite fraction increased from 60.42% to 99.64%. The X-ray diffractions showed that kaolinite was a major phase with FCC Bravais crystal lattice with particle sizes ranging between 14.6 nm and 92.5 nm. The particle size varied with intercalation ratios with methanol intercalated kaolinite > DMSO-kaolinite > urea-kaolinite (KPDMU). Following intercalation, SEM analysis revealed a change of order from thick compact overlapping euhedral pseudohexagonal platelets to irregular booklets which later transformed to vermiform morphology and dispersed euhedral pseudohexagonal platelets. Besides, dispersed euhedral pseudohexagonal platelets were seen to coexist with blocky-vermicular booklets. In addition, a unique brain-form agglomeration which transformed into roundish particles mart was observed after encapsulation. The nanocomposites decomposed between 48 and 600°C. Release profiles showed that 100% of urea was released in 97 hours from KPDMU while 87% was released in 150 hours from the encapsulated nanocomposite. The findings established that it is possible to use Pugu kaolinite and gum arabic biopolymer to prepare urea CRF formulations.